Verification of the Determination Method of Dissolved Metal Content using ICP-OES and Its Application for River Water in Bandar Lampung City - Ni Luh Gede Ratna Juliasih; Diky Hidayat; Purna Pirdaus; Rinawati Rinawati (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2021)
Method verification for metal analysis (Cd, Cr, Cu, Ni, Co, and Mn) in surface water using Inductively Coupled Plasma (ICP) was carried out to evaluate the method’s performance in the laboratory-based on US Method EPA 200.7. The verified method is used to determine the metal content in river water flowing in Bandar Lampung. The results showed that the method used had good linearity with a regression coefficient of more than 0.995. This method’s accuracy is expressed by the %RSD (relative standard deviation), which is in the range of 3.145 to 4.345% and meets the acceptance requirements with a %RSD value less than ⅔ CV Horwitz. The method accuracy obtained from the spiking analysis gives a range of 80-110% for the analysis of 1 mg/L and meets the acceptability required by AOAC. Overall, the performance of the method used is suitable for the analysis of metals in surface water. This method was applied for metal analysis in river water samples in several places in Bandar Lampung, which were the Palang Besi river (A1), the Way Balau Kedamaian river (B1), the Way Balau Kedaton river (C1), the Way Kuala river (D1), the Sumur Batu Kahuripan river (E1), Sumur Putri river (F1), and Muara Kahuripan river (G1). The concentrations of Cd, Cr, Cu, Ni, and Co metals were under the LoD method, while the Mn concentration was above the LoD method in river water samples.